Three Dimensional Internal Inclined Crack Growth Behavior due to Repeated Rolling Thermoelastic Contact Considering Friction of Crack Surface - ISHIHARA, Sotomi; SHIMIZU, Masayoshi; GOSHIMA, Takahito; UCHIYAMA, Ryuji (Transactions of the Japan Society of Mechanical Engineers Series A, 2005)
This paper considered three dimensional internal inclined crack growth behaviors due to repeated rolling thermoelastic contact. In this analysis, crack is modeled as an internal inclined planar crack in a three dimensional half-space. Rolling contact is simulated as a long and narrow distributed load with both normal and shear components moving with constant velocity. In comparing the shearing force with the frictional force of crack surface, the phenomenon of stick and slip were considered. At first, stress intensity factors along the crack contour are analyzed using high carbon chromium bearing steels. Next, numerial results of crack growth contours are given based on a modified Paris power low. And fatigue life is estimated by maximum crack growth. The shapes of crack contour and fatigue life are calculated under various conditions, which change sliding ratio, frictional coefficient, angle of inclined crack and friction coefficient of crack surface. As results, when the friction of crack surface is large, the crack progresses greatly in the direction at no friction of crack.